THE MENTAL TRAINING INFLUENCE IN STRENGTH GAINS AFTER FOUR WEEKS OF PRACTICE (Fiep Bulletin - online, 2014)
Mental imagery training consists of mentally repeating an imagined movement many times with the intention to improve motor performance (JEANNEROD, 1994). The purpose of this investigation is to verify if mental training helps to increase muscular strength after four weeks of training. Twenty eight male, young adults, with experience in strength training participated in this study. After 1-RM for bench press, subjects were randomly separated in two groups, strength training (G1) and mental imagery training (G2). They trained for 4 weeks, 3 days a week, 3 sets of 4 to 5 repetitions with 90% of their maximal repetition. The G2 had mental imagery training before the strength training and during the intervals. Results demonstrated better gains for G2 (9,6%) than G1 (5,4%), what indicates that mental imagery training is a good strategy for better gains in strength training programs.